Needs assessment for master of nursing programmes among Bangladesh nurses. (March 2016) - Lee, T.W.; Kim, H.S.; Kim, S.; Chu, S.H.; Kim, M.S; Lee, S.J.; Lim, S.; Jeon, Y.; Park, H.J.; Anowar, M.N.; Begum, T.
Abstract : Aim: This study aimed to assess the intent to enrol in a master of nursing programme among Bangladesh nurses, identify preferred programme options and measure the association among intent to enrol in the programme, clinical competency and job satisfaction. Background: Personal and professional aspects of potential students pursuing graduate education are beneficial in devising educational strategies. However, considering the pressing needs for higher nursing education, there are no masters of nursing programmes in Bangladesh. Methods: This study used a descriptive correlational design. Nurses working in Bangladesh public sector were recruited to participate in a self‐administered survey ( n  = 260). The questionnaire consisted of perception of job satisfaction, clinical competency and the need for educational options, including the intent to enrol in a master of nursing programme, preferred specialty area, curriculum content and career goals after graduation. Data were analysed using descriptive statistics and point‐biserial correlation. Results: Ninety per cent of the respondents reported that they intended to enrol in a master of nursing programme. Intention was significantly correlated with clinical competency but not with job satisfaction. The most preferred specialty areas were nursing management and education. Half of the respondents responded that teaching at nursing schools was a career goal after graduation. Discussion: The results of the needs assessment for the programme reflected the unique interest and priorities of the current status of Bangladesh. Conclusions: The results indicate a strong motivation to enrol in a master of nursing programme, confidence in clinical competence and high demand for programme in nursing management and education. These findings should be considered to design the programme in order to meet the interest of Bangladesh nurses. Implications for nursing and health policy: Educational needs assessments should take precedence to ensure the best possible educational outcome and to produce competent nurses who will contribute in achieving the Millennium Development Goals of Bangladesh.